IMPLEMENTASI KEBIJAKAN E-WARUNG PROGRAM KELUARGA HARAPAN DALAM UPAYA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Alie Zainal Abidin; Riskiyah Riskiyah; Yuni Hartono (STIA MALANG, 2023)
The implementation of the E-warung PKH program in Sumenep Regency refers to the Regulation of the Ministerof Social Affairs of the Republic of Indonesia Number 25 of 2016 concerning Assistance for the Development ofBusiness Facilities through Electronic Warung Gotong Royong Joint Business Group Family Hope Program (EWarung KUBE PKH). The E-warung program is a government system that provides financial assistance tounderprivileged communities to improve their welfare. This study aims to evaluate the implementation of thePKH E-warung Program in Sumenep Regency by taking into account policy targets, characteristics ofimplementing actors, available resources, attitudes of implementers, organizational discourse, and socialeconomic aspects. The research method used is descriptive with a qualitative approach. The results showed thatthe implementation of the PKH E-warung Program at the Sumenep Regency Social Office was quite optimal.However, there are several problems that often arise, such as delays in aid funds that do not enter the beneficiaries'Family Welfare Card (KKS) accounts every month, and lack of funds for making proof of food receipts forbeneficiary families. Welfare in this context refers to meeting the material, spiritual, and social needs of thecommunity in order to live a decent life and be able to develop one's potential. In addition, there are often networkproblems on Electronic Data Capture (EDC) machines. Based on the conclusions of the study, the researcherrecommended that program implementers, especially Bank Mandiri and the central government, provide separatefunds for making proof of food receipts for beneficiary families in each E-warung, so that all parties get fair andequitable treatment.